The Mass observers a history, 1937-1949 - Hinton, James (Oxford University Press, 2013)
"This is the first full-scale history of Mass-Observation, the independent social research organisation which, between 1937 and 1949, set out to document the attitudes, opinions, and every-day lives of the British people. Through a combination of anthropological fieldwork, opinion surveys, and written testimony solicited from hundreds of volunteers, Mass-Observation created a huge archive of popular life during a tumultuous decade which remains central to British national identity. The social history of these years has been immeasurably enriched by the archive, and extracts from the writings of M-O's volunteers have won a wide and admiring audience. Now James Hinton, whose acclaimed Nine Wartime Lives demonstrated how the intensely personal writing of some of M-O's volunteers could be used to shed light on broader historical issues, has written a wonderfully vivid and evocative account which does justice not only to the two founders whose tempestuous relationship dominated the early years of Mass-Observation, but also to the dozens of creative and imaginative, and until now largely unknown, young enthusiasts whose work helped to keep the show on the road. The history of the organisation itself - the staff, the research methods, the struggle for funding, M-O's characteristic 'voice', and its role in the cultural and political life of the period - are themselves as interesting as any of the themes that the founders set out to document. This long-awaited and deeply researched history corrects and revises much of our existing knowledge of Mass-Observation, opens up new and important perspectives on the organisation, and will be seen as the authoritative account for years to come."--Publisher's website